1995
DOI: 10.1097/00005392-199507000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Luteinizing Hormone-Releasing Hormone Agonist Leuprolide on Lipoproteins, Fibrinogen and Plasminogen Activator Inhibitor in Patients with Benign Prostatic Hyperplasia

Abstract: The impact of chronic administration of the luteinizing hormone-releasing hormone agonist leuprolide depot on cardiovascular risk factors was investigated in a controlled double-blind study comprising 50 evaluable patients with benign prostatic hyperplasia. In the 26 patients receiving leuprolide the mean total cholesterol level increased by 10.6%, high density lipoprotein cholesterol by 8.2% and triglycerides by 26.9% (p = 0.003, 0.052 and 0.050, respectively). Low density lipoprotein cholesterol levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
24
1
Order By: Relevance
“…9 GnRH agonists also increase serum triglycerides and low density lipoprotein cholesterol. 5,8,10 Consistent with these adverse metabolic effects, GnRH agonists are associated with greater risk of incident diabetes mellitus and cardiovascular disease in men with prostate cancer. 11…”
Section: Introductionmentioning
confidence: 97%
“…9 GnRH agonists also increase serum triglycerides and low density lipoprotein cholesterol. 5,8,10 Consistent with these adverse metabolic effects, GnRH agonists are associated with greater risk of incident diabetes mellitus and cardiovascular disease in men with prostate cancer. 11…”
Section: Introductionmentioning
confidence: 97%
“…21 In their study, Eri et al evaluated the impact of the luteinizing hormone-releasing hormone (LHRH) agonist leuprolide on 26 patients with benign prostatic hyperplasia (BPH) and showed that the mean total cholesterol level increased by 10.6%, HDL cholesterol by 8.2%, and triglycerides by 26.9%, but LDL levels were unchanged. 27 Smith et al in their study on 26 men treated with leuprolide for 12 months showed the same increase in HDL levels. 28 In our study, the mean amount of trigycerides in patients significantly increased after both six and 12 months.…”
Section: Adt and Hyperlipidemiamentioning
confidence: 69%
“…8,[25][26][27][28] ADT significantly increases fat mass, decreases lean body mass, 29,30 increases fasting plasma insulin and decreases insulin sensitivity 31 and increases serum cholesterol and triglyceride levels. 29,32,33 There are limitations in this current study. Firstly, the study was conducted in a single city in British Columbia.…”
Section: Wallis Et Almentioning
confidence: 91%